2020
DOI: 10.1007/s12471-020-01465-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the MANTA closure device in transfemoral transcatheter aortic valve replacement: a single-centre observational study

Abstract: Objectives The present study aims to evaluate the efficacy and safety of the MANTA vascular closure device (VCD) (Teleflex, Morrisville, NC, USA) in transfemoral transcatheter aortic valve replacement (TF-TAVR). Background To close the femoral artery in TF-TAVR a VCD is the treatment of choice. Data involving suture-based VCDs have been extensive. Although scarce, results on the MANTA device are promising. There is no consensus yet as to whether the MANTA device is associated with fewer access-site-related vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“… 25 In our current and previous studies of the US-MANTA technique, 14 the rates of major VCs (1.9 and 1.5%, respectively) were in the lower range of those reported in previous studies. 8 - 14 , 24 Also, our previous study demonstrated a propensity score-matched comparison between US-MANTA versus conventional MANTA, which concluded that the US-guided technique was an independent predictor of less frequent access-site major vascular complications. 14 These results suggest that the ultrasound-guided technique might be beneficial.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 25 In our current and previous studies of the US-MANTA technique, 14 the rates of major VCs (1.9 and 1.5%, respectively) were in the lower range of those reported in previous studies. 8 - 14 , 24 Also, our previous study demonstrated a propensity score-matched comparison between US-MANTA versus conventional MANTA, which concluded that the US-guided technique was an independent predictor of less frequent access-site major vascular complications. 14 These results suggest that the ultrasound-guided technique might be beneficial.…”
Section: Discussionmentioning
confidence: 98%
“…24 However, the incidence of major VCs with MANTA still varied from 0% to 11%, which could be depending on the population and procedural variance included in the studies. [8][9][10][11][12][13]24 When comparing a suture-based VCD with and without ultrasound following TAVR, the ultrasound-guided technique significantly reduced VC. 25 In our current and previous studies of the US-MANTA technique, 14 the rates of major VCs (1.9 and 1.5%, respectively) were in the lower range of those reported in previous studies.…”
Section: Efficacy Of Ultrasound-navigated Manta Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Netherlands Heart Journal , Halim et al. report the results of a single-centre study assessing the efficacy and safety of the use of the MANTA large-bore vascular closure device in transfemoral transcatheter aortic valve replacement (TF-TAVR) [ 1 ]. The MANTA closure device showed promise in these patients, although a considerable proportion of them had access-site-related vascular complications.…”
mentioning
confidence: 99%
“…The outcomes of earlier studies [ 2 7 ] are in line with those reported by Halim et al., describing a prevalence of access-site-related vascular complications—as defined by the Valve Academic Research Consortium-II criteria [ 8 ]—ranging from 2–14%. The authors correctly identified a steep learning curve when using the MANTA device, even though they did not analyse this [ 1 ]. Hoffman et al.…”
mentioning
confidence: 99%